Epidemiology and genetic characteristics of Clostridioides difficile isolates in Northwest China - Yang Li; Shujuan An; Hongjia Sun; Meimei Hu; Yanmei Xu; Yaming Xi (PeerJ)
Clostridioides difficile (C. difficile) is a significant hospital-acquired pathogen that can cause antibiotic-associated diarrhea. In this study, we investigate the epidemiological and genetic characteristics of C. difficile isolates from a tertiary hospital in Northwest China. We prospectively collected fecal samples from 212 patients with diarrhea between January 2023 and May 2024 at the First Hospital of Lanzhou University. Twenty-five (11.8%, 25/212) strains of C. difficile were isolated, and twenty (9.4%, 20/212) were identified as toxigenic C. difficile (TCD). The dominant toxin gene profiles were tcdA+ B+ (80%, 20/25). Furthermore, twelve different sequence types (STs) belonging to three clades were identified, and the most prevalent types were ST3 followed by ST2 and ST35. Toxin variant analysis revealed the presence of eight types of tcdA variants and seven types of tcdB variants, most tcdA/B variants corresponded to specific ST types. Phylogenetic analysis based on single nucleotide polymorphisms (SNPs) further confirmed the genetic diversity and relationships among isolates. We identified 13 resistance genes, including mutations in gyrA/gyrB (96% of strains) and rpoB (72%), conferring resistance to fluoroquinolones and rifamycins, respectively. The study provides valuable insights into the epidemiological and genetic features of C. difficile in Northwest China, guiding future prevention and control measures.